Functional and genomic analyses of plant growth promoting traits in Priestia aryabhattai and Paenibacillus sp. isolates from tomato rhizosphere - Carolina Almirón; Tomás Denis Petitti; María Agustina Ponso; Ana María Romero; Vanessa Andrea Areco; María Isabel Bianco; Martín Espariz; Pablo Marcelo Yaryura (Scientific Reports)
Abstract This study investigated plant growth-promoting (PGP) mechanisms in Priestia aryabhattai VMYP6 and Paenibacillus sp. VMY10, isolated from tomato roots. Their genomes were initially assessed in silico through various approaches, and these observations were then compared with results obtained in vitro and in vivo. Both possess genes associated with the production of siderophores, indole acetic acid (IAA) and cytokinins (CKs), all of which have been shown to promote plant growth. The two strains were able to produce these compounds in vitro. Although both genomes harbor genes for phosphorus solubilization, only VMY10 demonstrated this ability in vitro. Genes linked to flagellar assembly and chemotaxis were identified in the two cases. Both strains were able to colonize plant roots, even though VMYP6 lacked motility and no flagella were observed microscopically. In the greenhouse, tomato plants inoculated with the strains showed increased biomass, leaf area, and root length. These findings underscore the importance of integrating in vitro assays, genomic analyses, and plant trials to gain a comprehensive insight into the PGP mechanisms of rhizobacteria like VMYP6 and VMY10. Such insight may contribute to improving the selection of strains used as biofertilizers in tomato, a major crop worldwide.